Capparis spinosa leaves extract: Source of bioantioxidants with nephroprotective and hepatoprotective effects - Tlili, Nizar; Feriani, Anouar; Saadoui, Ezzeddine; Nasri, Nizar; Khaldi, Abdelhamid (Biomedicine & pharmacotherapy, 2017)
Capparis spinosa, Capparidaceae, is largely distributed all over the Mediterranean Basin and is traditionally used to treat many illnesses, such as liver and kidney diseases. The aim of the current study was to explore the antioxidant, nephroprotective and hepatoprotective effects of methanolic extract of Capparis spinosa leaves (MECS) associated with its phytochemical content. The levels of total phenolics, flavonoids and condensed tannins were 23.37mgGAE/g, 9.05mgQE/g and 9.35mgTAE/g, respectively. HPLC analysis revealed nine compounds, namely rutin, resveratrol, coumarin, epicatechin, luteolin, catechin, kaempferol, vanillic acid and gallic acid. The MECS showed interesting antioxidant capacity. The MECS-treatment significantly reduced the increased plasma levels of creatinine, urea and uric acid, reduced the elevated MDA levels, significantly reduced the antioxidant enzyme activities and restored the kidney damage, provoked by cisplatin-treatment. Furthermore, MECS-treatment significantly prevented the increase in serum ALT, AST and LDH levels in acute liver damage induced by CCl4, decreased the amount of hepatic malondialdehyde (MDA) formation and elevated the activities of SOD, CAT and GPx, and restored liver injury. This study supports the traditionally use of C. spinosa to cure kidney and liver diseases. The obtained results highlighted the possible use of C. spinosa as a source of phytochemical with important biological advantages.